Implementasi Strategi Pembelajaran Berbasis Taksonomi SOLO untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Geografi (Studi Kasus di SMAN 25 Bandung) - Jajang Sudrajat; Sri Handayani; Eva Dianawati Wasliman (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
21st century education requires the development of Higher Order Thinking Skills (HOTS), especially critical thinking skills, but the achievement of Indonesian students is still relatively low. This study aims to examine the implementation of SOLO Taxonomy-based learning strategies in improving students' critical thinking skills in geography subjects at SMAN 25 Bandung. This study uses a qualitative approach with a case study design. The main informant consisted of two geography teachers. Data was collected through in-depth interviews, learning observations, and document analysis, then analyzed thematically using an interactive model. To strengthen the perspective of education administration, the findings were analyzed using the CIPP (Context, Input, Process, Product) model framework. The results of the study show that learning planning has been systematically prepared and directed at developing the quality of students' thinking. The organization of learning places teachers as facilitators and students as active subjects, even though it is not yet fully institutionalized in the school system. The implementation of learning encourages students to reach the level of relational and extended abstract thinking, although they still face time constraints and heterogeneity of abilities. The evaluation has used a SOLO taxonomy-based rubric, but it needs to be developed again as feedback. This study concludes that the SOLO Taxonomy-based learning strategy has the potential to improve students' critical thinking skills if supported by careful planning, structured organization, and integrative evaluation.